(untitled) (Praxis Educativa, 2026)
The educational dimension of territory entails the analysis of the existence, appropriation, organization, and modes of structuring teaching and learning processes across multiple instances, resources, and spaces associated with lifelong education. In this regard, questions arise concerning the characteristics of the educational spaces that take place within a given territory, as well as their challenges, needs, and issues in relation to the exercise of the right to lifelong education for the entire population. The findings presented in this article seek to begin addressing these questions through an analysis of the supply of and demand for literacy education and primary-level completion among young people and adults in the First Section of the Tigre Islands, in the Paraná Delta, Province of Buenos Aires, based on a diagnostic study conducted between 2023 and 2025.